The K-3 Guide to Academic Conversations : Practices, Scaffolds, and Activities - Zwiers, Jeff; Hamerla, Sara R. (Corwin, 2017)
"For thousands of years people have been using the skills we describe in this book to engage in conversations with others. What isn't as prevalent, however, is instruction--especially in primary grades-in which we engage students in productive conversations about academic ideas. This book fills that very big need." --Jeff Zwiers & Sara Hamerla Talk about content mastery . . . Primary teachers, you won't want to miss this: if you're looking for a single resource to foster purposeful content discussions and high-quality interpersonal engagement, then put Jeff Zwiers and Sara Hamerla's K-3 Guide.